Archaeology under the shadow of swastika - Aleksandar Bandović (University of Belgrade, 2016)
Graben für Germanien. Archäologie unterm Hakenkreuz. 2013. Focke-Museum (Hrgs.) Stuttgart: Theiss Verlag, pp. 216.